Deciphering acute coronary syndrome biomarkers: High-resolution proteomics in platelets, thrombi and microparticles. (2nd January 2017) - Navas-Carrillo, Diana; Marín, Francisco; Valdés, Mariano; Orenes-Piñero, Esteban
Abstract: Acute coronary syndromes (ACS) encompass unstable angina, non-ST segment elevation myocardial infarction, ST-segment elevation myocardial infarction and sudden cardiac death. They are commonly associated with the presence of vulnerable plaques in the coronary arteries and occur when a thrombus formed from a ruptured atheromatous plaque causes a prolonged occlusion of a coronary artery. The erosion of the vulnerable plaques results in the formation of luminal thrombi secondary to platelet activation and the release of thrombogenic elements within the atherosclerotic lesions. Proteomic approaches offer an unbiased platform for the comprehensive analysis of the whole proteome in a certain physiological time. Although mRNA expression is widely considered to be indicative of protein expression, protein levels are the result of protein synthesis and degradation, and RNA levels are not informative of protein degradation. In contrast, the proteomic technology investigates protein expression directly. This is particularly important in the context of atherosclerosis in which protein degradation is as decisive as protein synthesis. Moreover, proteomics reveals post-translational modifications known to be determinant for many human diseases. Clinically, there is increasing evidence for the role of proteomic technology in biomarker discovery that will provide novel information on the molecular events associated with ACS, and potentially lead to the identification of novel drug targets. In this review, we describe in detail the importance of proteomic approaches to identify new biomarkers associated with ACS from three perspectives: biomarkers associated with platelet metabolism; the study of proteomics of intravascular thrombi; and proteome analysis of membrane microparticles released from activated cells, mostly by platelets.